Bioengineered 3D Tissue Model of Intestine Epithelium with Oxygen Gradients to Sustain Human Gut Microbiome. Issue 16 (19th June 2022) - Chen, Ying; Rudolph, Sara E.; Longo, Brooke N.; Pace, Fernanda; Roh, Terrence T.; Condruti, Rebecca; Gee, Michelle; Watnick, Paula I.; Kaplan, David L.
Abstract: The human gut microbiome is crucial to hosting physiology and health. Therefore, stable in vitro coculture of primary human intestinal cells with a microbiome community is essential for understanding intestinal disease progression and revealing novel therapeutic targets. Here, a three‐dimensional scaffold system is presented to regenerate an in vitro human intestinal epithelium that recapitulates many functional characteristics of the native small intestines. The epithelium, derived from human intestinal enteroids, contains mature intestinal epithelial cells and possesses selectively permeable barrier functions. Importantly, by properly positioning the scaffolds cultured under normal atmospheric conditions, two physiologically relevant oxygen gradients, a proximal‐to‐distal oxygen gradient along the gastrointestinal (GI) tract, and a radial oxygen gradient across the epithelium, are distinguished in the tissues when the lumens are faced up and down in cultures, respectively. Furthermore, the presence of the low oxygen gradients supported the coculture of intestinal epithelium along with a complex living commensal gut microbiome (including obligate anaerobes) to simulate temporal microbiome dynamics in the native human gut. This unique silk scaffold platform may enable the exploration of microbiota‐related mechanisms of disease pathogenesis and host‐pathogen dynamics in infectious diseases including the potential to explore the human microbiome‐gut‐brain axis and potential novel microbiome‐based therapeutics. Abstract : Scaffold system is developed to engineer in vitro human intestinal epithelium that recapitulates many functional characteristics of the in vivo small intestines. By properly positioning the scaffolds cultured under normal atmospheric conditions, physiologically relevant oxygen profiles are generated which support host‐gut microbiome cocultures and simulate temporal microbiome dynamics.